2020
DOI: 10.1002/mnfr.202000591
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Nutritional Composition of a Biotechnologically Produced Oyster Mushroom and its Physiological Effects in Obese Zucker Rats

Abstract: Scope: Sustainable protein sources are needed to meet the increasing protein demands of a continuously growing world population. This study is focused on the biotechnological production of a protein rich oyster mushroom (Pleurotus sajor-caju; PSC) by valorization of an agricultural side stream and the evaluation of the physiological effects of PSC in a rat model of metabolic syndrome. Methods and results: PSC is produced via submerged cultivation in a 150 L bioreactor that utilizes isomaltulose molasses as its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(41 citation statements)
references
References 81 publications
6
35
0
Order By: Relevance
“…8 We also found that the lowering of hepatic lipids was accompanied by a reduction of hepatic inflammation and systemic inflammatory parameters. 8 However, the reason underlying the pronounced antisteatotic and anti-inflammatory effect of P. sajor-caju supplementation remains to be shown.…”
Section: ■ Introductionmentioning
confidence: 55%
See 3 more Smart Citations
“…8 We also found that the lowering of hepatic lipids was accompanied by a reduction of hepatic inflammation and systemic inflammatory parameters. 8 However, the reason underlying the pronounced antisteatotic and anti-inflammatory effect of P. sajor-caju supplementation remains to be shown.…”
Section: ■ Introductionmentioning
confidence: 55%
“…For this investigation, liver, plasma, and colonic digesta samples from a recently described animal study that utilized Zucker rats were used. 8 The animal experiment was approved by the local Animal Care and Use Committee (Regierungsprasidium Giessen; permission no: JLU 648_M). All experimental procedures outlined followed established guidelines for the care and handling of laboratory animals.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These include the association of increased mushroom consumption with decreased risks of dementia [ 133 , 134 ], cardiovascular disease, certain cancers (e.g. prostate and breast cancer) [ 135 , 136 ], IBD [ 137 ], metabolic syndrome [ 138 ], PD and other neurological disorders [ 139 ], viral infections [ 140 ] and many other conditions. Some of the studies attributed these perceived health benefits of mushrooms to the ET present [ 129 , [141] , [142] , [143] ].…”
Section: Sources Of Ergothioneinementioning
confidence: 99%